If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6v + -6(8 + 2v) = 7v + 30 6v + (8 * -6 + 2v * -6) = 7v + 30 6v + (-48 + -12v) = 7v + 30 Reorder the terms: -48 + 6v + -12v = 7v + 30 Combine like terms: 6v + -12v = -6v -48 + -6v = 7v + 30 Reorder the terms: -48 + -6v = 30 + 7v Solving -48 + -6v = 30 + 7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-7v' to each side of the equation. -48 + -6v + -7v = 30 + 7v + -7v Combine like terms: -6v + -7v = -13v -48 + -13v = 30 + 7v + -7v Combine like terms: 7v + -7v = 0 -48 + -13v = 30 + 0 -48 + -13v = 30 Add '48' to each side of the equation. -48 + 48 + -13v = 30 + 48 Combine like terms: -48 + 48 = 0 0 + -13v = 30 + 48 -13v = 30 + 48 Combine like terms: 30 + 48 = 78 -13v = 78 Divide each side by '-13'. v = -6 Simplifying v = -6
| 4x^2-7x+1=x+1 | | 6r+13=13+7r | | 45g^2+12g-9=0 | | 9(-10)-5x-19=21 | | 3(7s+6)-17s=2(2s+4)-11 | | 2a^2c^3-14bc^3+32c^3d^2=0 | | 4u+7v-6(7u-7v)= | | 8g-2=5g+10 | | 12(n)=180(n-2) | | 3x+50=5x-25 | | 18x^2=48x-3 | | -18x^2-18x+8=0 | | x^2-13x+39=-3 | | 4(c-2)+9=5+c-4 | | 0=-7z | | x+1-1+2=x+3-1+x | | 432+26x+(2)9x=399 | | 3y-1+y=0 | | 5/4(-4/3)+1/2=2(-4/3)-1/2 | | 11=-3y-4 | | 8t+4=2(4t-3) | | X^3+x=175 | | -156=5-7(2v+7) | | 7x^2+52x+21=0 | | 256z^2-4-192z^2+3=0 | | -5=f+4 | | 5/4(3/4)+1/2=2(3/4)-1/2 | | 9y+1=1y+25 | | 12=-2y-4x | | 5/4(-1/2)+1/2=2(-1/2)-1/2 | | (x-3-4i)(x-3+4i)= | | .25m+5=8 |